2019
DOI: 10.1186/s12967-019-1837-z
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA modification and its writer/reader VIRMA/YTHDF3 in testicular germ cell tumors: a role in seminoma phenotype maintenance

Abstract: BackgroundCovalent RNA modifications, such as N-6-methyladenosine (m6A), have been associated with various biological processes, but their role in cancer remains largely unexplored. m6A dynamics depends on specific enzymes whose deregulation may also impact in tumorigenesis. Herein, we assessed the differential abundance of m6A, its writer VIRMA and its reader YTHDF3, in testicular germ cell tumors (TGCTs), looking for clinicopathological correlates.MethodsIn silico analysis of TCGA data disclosed altered expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 65 publications
5
67
1
Order By: Relevance
“…In seminoma, YTHDF3 and VIRMA are significantly overexpressed and there is a positive correlation between their expression [95].…”
Section: Ythdf3mentioning
confidence: 96%
“…In seminoma, YTHDF3 and VIRMA are significantly overexpressed and there is a positive correlation between their expression [95].…”
Section: Ythdf3mentioning
confidence: 96%
“…As the best characterized as m6A "readers", YTH domain containing family 1 (YTHDF1) promotes translation efficiency by binding m6A-modified mRNA [29], whereas YTHDF2 decreases mRNA stability and facilitates mRNA degradation [30]. YTHDF3 facilitates translation and decay of m6A-modified mRNAs through cooperation with YTHDF1 and YTHDF2 [31]. Next, we further investigated whether LPS stimulation-promoted upregulation of GNAS mRNA is related to m6A modification.…”
Section: Lps-induced Il-6 Expressionmentioning
confidence: 99%
“…Recent studies have found that METTL3 can regulate mRNA structure independently of its m6A catalytic activity, thus promoting oncogene translation [70] .KIAA1429 also given the name :virus , just similar to m6A methyltransferase related gene. It is reported that KIAA1429 promotes the multiplication , shift and invasion of liver cancer via modulating the mRNA methylation level where cell line was situated Id2 [30] .Also,A study expressed that KIAA1429 presented signi cant up-regulation in seminoma and down-regulation in the non-tumours [71] . KIAA1429, which features high expression on breast cancer , is able to enhance the multiplication and metastasis of breast cancer not only in vivo but also in vitro [72] .…”
Section: Discussmentioning
confidence: 94%